2015
DOI: 10.1007/s00268-015-3370-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Transfusion Strategy in Acute Non‐variceal Upper Gastrointestinal Bleeding: A Nationwide Study of 5861 Hospital Admissions in Denmark

Abstract: PRBC transfusion was associated with adverse events, including 30-day mortality and failure of hemostasis. In contrast, transfusion of PLT was associated with a reduction in need for re-endoscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…A retrospective nationwide survey of 5861 hospital admissions in Denmark showed that the number of units of red blood cells is a predictor of the need for repeated endoscopy, surgery and 30-day mortality. 19 In Canada, a retrospective cohort of 1677 patients with UGIB found that transfusion of red blood cells within 24 hours of presentation was significantly and independently associated with an increased risk of recurrent bleeding. 20 Another retrospective cohort from Australia, which included 2228 patients with NVUGIB, also reported that blood transfusion of more than four units is associated with increased risk of further bleeding, but not with higher mortality.…”
Section: Consensus Statementsmentioning
confidence: 99%
“…A retrospective nationwide survey of 5861 hospital admissions in Denmark showed that the number of units of red blood cells is a predictor of the need for repeated endoscopy, surgery and 30-day mortality. 19 In Canada, a retrospective cohort of 1677 patients with UGIB found that transfusion of red blood cells within 24 hours of presentation was significantly and independently associated with an increased risk of recurrent bleeding. 20 Another retrospective cohort from Australia, which included 2228 patients with NVUGIB, also reported that blood transfusion of more than four units is associated with increased risk of further bleeding, but not with higher mortality.…”
Section: Consensus Statementsmentioning
confidence: 99%
“…Limitations of FFP include the requirement for a higher volume load to achieve a reversal effect, slower onset of action compared with PCC, and requirement for blood group typing. In addition, recent evidence suggests that use of FFP is associated with increased mortality in patients undergoing endoscopy for NVUGIH [56][57][58]. Three-or four-factor PCC or FFP can be used when the reversal of anticoagulation is urgent because of patient hemodynamic instability or life-threatening massive bleeding, irrespective of INR values.…”
Section: Recommendationmentioning
confidence: 99%
“…A retrospective cohort study by Fabricius et al . 29 in 2016 showed that the risk of a second endoscopy increased by 8% and the risk of death within 30 days increased by approximately 4% whenever one unit of red blood was transfused. A subgroup analysis by Subramaniam et al .…”
Section: Bodymentioning
confidence: 99%